2020
DOI: 10.5195/jmla.2020.954
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions to improve literature searching skills in the health sciences: a scoping review

Abstract: Objective: The authors reviewed educational interventions for improving literature searching skills in the health sciences.Methods: We performed a scoping review of experimental and quasi-experimental studies published in English and German, irrespective of publication year. Targeted outcomes were objectively measurable literature searching skills (e.g., quality of search strategy, study retrieval, precision). The search methods consisted of searching databases (CINAHL, Embase, MEDLINE, PsycINFO, Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The findings of this systematic review build on the emerging evidence base exploring the effectiveness of different teaching strategies on the competency of EBP learners [ 9 15 ]. Results from this current review update and extend on the findings from our 2014 systematic review, which identified a small, albeit moderate quality of evidence, on the effectiveness of different training modalities in medical trainees [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this systematic review build on the emerging evidence base exploring the effectiveness of different teaching strategies on the competency of EBP learners [ 9 15 ]. Results from this current review update and extend on the findings from our 2014 systematic review, which identified a small, albeit moderate quality of evidence, on the effectiveness of different training modalities in medical trainees [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of systematic reviews published evaluating the effectiveness of interventions focused on teaching EBP. Some of these have addressed only one aspect of EBP such as literature searching [9], whilst others have focused on specific cohorts such as medical trainees [10], medical students [11], undergraduate health students [12], postgraduate teaching [13], or nursing programs [14].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that nurses who had previously attended EBP training programs had more knowledge than those who had not. Hirt et al [ 35 ] conducted a review study of educational interventions on health-related literature searching skills. They indicated that participants in the included studies were students and physicians from various health professions.…”
Section: Discussionmentioning
confidence: 99%
“…Further research on the efficacy of these interventions is also suggested by using controlled study designs and long-term follow-up. According to the findings of a review study [ 35 ], few educational interventional studies on search skills have been conducted in the last 10 years. Therefore, more emphasis must be placed on nurses' education.…”
Section: Discussionmentioning
confidence: 99%
“…There are many questions that could be asked, but the aim should be to find a focused question that is answerable (Coulbeck & Hadfield, 2013), and delivers findings that should improve the information literacy initiative. A good start to thinking around the problem would be to find a relevant scoping review, such as Hirt et al (2020) on educational interventions to improve literature searching skills in the health sciences. The review collates details about the research design, participants, the nature of the educational intervention and the outcome.…”
Section: Doing An Experiments To Test An Interventionmentioning
confidence: 99%